Synthesis of FeâLiâCr Multinuclear Complexes as Molecular Magnet Materials - Djulia Onggo; Iis Siti Jahro; Fahimah Martak; Ismunandar Ismu (Journal of Mathematical and Fundamental Sciences, 2008)
Multinuclear complexes have received considerable interest as molecular magnet materials. Up to now, several complex compounds based on bidentate ligand 2,2' bipyridine have been synthesized. In this research, the Fe-Li-Cr multinuclear complexes with derivative 2'2- bipyridine ligands: 2-(2'-pyridyl)quinoline(pq), 2,2'-Pyridil(pdl) have been synthesized. The oxalate (ox) ligand has also been used as a bridging ligand in these multinuclear complexes. The chemical formula of Li[FeCr(ox)2(pq)(BF4)2(H2O)2] and [Fe(pdl)n][LiCr(ox)3] complexes have been verified using metal and C, H, N elemental analysis data. The IR spectra in 350 "“ 4000 cm-1 range exhibit characteristic absorptions, which support the proposed structure of complex. The plausible structure of the compounds has been drawn based on complex formation mechanism. The magnetic susceptibility at room temperature of the pq-complex is about 5.7 BM and of the pdl- complexes are 4.8 and 5.5 BM. These indicated that both spin states of iron(II) exist in the multinuclear complexes.